Calculation of the turning trajectory of an unmanned vehicle with front steerable wheels - Sukharev R.Yu.; Belyaev K.V.; Lazuta I.V. (Научно-технический вестник Брянского государственного университета, 2025)
The trajectory of an unmanned vehicle can be represented by a set of elementary movements, one of which is a turn at a given angle. To calculate the turning trajectory, a calculation scheme was drawn up, a mathematical model of the movement of the machine and theoretical studies of the influence of the main design and operational parameters of the machine on the characteristics of the turning trajectory were carried out. As a result of the conducted research, analytical dependences of the length of the maneuver and the time of giving the signal on the speed of the machine, the length of its base and the set angle of rotation were obtained. The obtained dependencies allow us to calculate the coordinates of the maneuver start point and the duration of the steering control signal to perform the maneuver in accordance with a given trajectory.